2019
DOI: 10.3168/jds.2018-14881
|View full text |Cite
|
Sign up to set email alerts
|

Bacteriocin production by Lactobacillus plantarum ST16Pa in supplemented whey powder formulations

Abstract: Whey, the main by-product of the dairy industry, is frequently disposed of in the environment without any treatment due to the high cost of this process. Alternatively, whey can be used as a medium to culture lactic acid bacteria and produce value-added products such as bacteriocins. In this work, we attempted to improve bacteriocin production by Lactobacillus plantarum ST-16Pa in a whey powder formulation supplemented with additional sources of carbon, nitrogen, and vitamin B 12 at different levels and varyin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 48 publications
2
20
0
3
Order By: Relevance
“…Bacteriocins produced by lactic acid bacteria are usually growth‐dependent metabolites, regulated by environmental conditions as well as the productive strain's growth phase (Papagianni & Papamichael, 2011; Sabo, Converti, Ichiwaki, & Oliveira, 2019). The findings of this study revealed that concerning the isolated strain ( L. plantarum ), the bacteriocin production initiates in the early log phase, and as the process goes on, this feature progresses up to 3,200 AU/ml, suggesting the bacteriocin is highly likely a primary metabolite.…”
Section: Discussionmentioning
confidence: 99%
“…Bacteriocins produced by lactic acid bacteria are usually growth‐dependent metabolites, regulated by environmental conditions as well as the productive strain's growth phase (Papagianni & Papamichael, 2011; Sabo, Converti, Ichiwaki, & Oliveira, 2019). The findings of this study revealed that concerning the isolated strain ( L. plantarum ), the bacteriocin production initiates in the early log phase, and as the process goes on, this feature progresses up to 3,200 AU/ml, suggesting the bacteriocin is highly likely a primary metabolite.…”
Section: Discussionmentioning
confidence: 99%
“…Biomass specific growth rate (μ) was estimated from the experimental data of biomass concentration by the equation (Sabo et al, 2019):…”
Section: Methodsmentioning
confidence: 99%
“…Além do fato de esses micro-organismos serem considerados culturas iniciadoras em processos de fermentação, eles também conferem característica de preservação aos alimentos, aumentando a vida-de-prateleira (Sabo et al, 2019).…”
Section: Lactobacillus Mesenteroides Lactobacillus Cremoris Lactobaunclassified
“…Este composto antimicrobiano é produzido por diversos outros microorganismos; entretanto, quando produzido pelas BAL, vem recebendo maior atenção pelo fato deste grupo de bactérias geralmente apresentarem segurança para consumo humano (Sabo et al, 2019;Balciunas et al, 2013).…”
Section: Lactobacillus Mesenteroides Lactobacillus Cremoris Lactobaunclassified
See 1 more Smart Citation